Alison Bechdel and The Secret of Superhuman Strenght: The Return of a Pioneer - Jiménez, Jesús (Filanderas, 2022)
Some people seem ahead of their time, and Alison Bechdel and Alison Bechdel (Pennsylvania, 1960) is one of them, as she proves once again with her latest work: The Secret of Superhuman Strength. In it she discusses issues such as physical decline and menopause, which should be commonplace in fiction, but are still taboo subjects.